انفراد سورة إبراهيم بذكر أدعية إبراهيم عليه السلام دون قصته: دراسة تحليلية : (The Uniqueness of Surah Ibrahim in Mentioning the Supplications of Prophet Ibrahim (Peace Be Upon Him) Without His Story: An Analytical Study) - فاطمة سعد النعيمي (At-Tajdid - Intellectual Refereed Journal, 2025)
This research explores the unique phenomenon of Surah Ibrahim focusing exclusively on the supplications of Prophet Ibrahim (peace be upon him), without narrating the details of his life story, unlike other Qur’anic chapters that present various aspects of his journey. The study aims to analyze these supplications to understand their rhetorical and educational implications and to examine their connection to the main themes of the Surah, such as the call to monotheism, gratitude for divine blessings, and reliance on God. The importance of the study lies in highlighting the pedagogical and spiritual value of prophetic supplications in the Qur’an and the rhetorical uniqueness of the Surah’s approach, thus enriching Qur’anic scholarship related to prophetic prayers. The research problem centers on understanding the wisdom behind this focus on supplication rather than narrative, seeking to answer questions about the nature, dimensions, and structural role of these prayers within the Surah. The study employs analytical, inferential, and comparative methodologies, concluding that this exclusive focus serves a deliberate rhetorical purpose that deepens the Surah’s messages of faith and monotheism, and underscores the profound educational role of supplication. Keywords: Surah Ibrahim, Supplications of Ibrahim, Monotheism, Gratitude, Qur’anic Rhetoric, Faith-Based Education